The vertical structure and variability of currents east of Philippines from mooring measurements during the 2015/2016 El Niño - Liu, Yansong; Ren, Qiang; Yu, Fei; Wei, Chuanjie; Diao, Xinyuan; Nan, Feng (Frontiers in Marine Science, 2023)
We investigated the mean vertical structure and variability of the currents along the western boundary of the Philippines using mooring observations at about 8°N, 127°E from August 2014 to January 2016. The southward Mindanao Current (MC) exists in the upper 600 m countered by the northward Mindanao Undercurrent (MUC) observed below 600 m to the depth of 2,000 m, with a core at approximately 1,000 m. During the development of El Niño from July to December 2015, the core velocity and depth of the MC were noticeably increased, consistent with the Niño 3.4 index, and the current at 2,000 m was observed to be southward, consistent with the MC, which indicated that the MC is able to extend to 2,000 m under the influence of El Niño. The MUC was stronger in November 2014 and November 2015, corresponding to the peak phase of the Niño 3.4 index. The intraseasonal variability with a period of 70-110 days from the surface to 2,000 m is also discussed based on power spectral analysis.